A violência sexual e seus discursos: um estudo de caso - Souza, Lívia Pereira de (2013)
This is a master thesis linked to the research area Violence, Crime and Public Security , from de Post-Graduation Program in Criminal Sciences from Pontifícia Universidade Católica do Rio Grande do Sul, Brazil. Its main goal is the analysis of discourses regarding sexual violence. In order to limit the scope of the analysis, one case of sexual violence occurred in the city of Porto Alegre, Brazil, was selected. The work starts with a clarification of what it understands as discourse analysis . It presents the two theories employed in the analysis, the theories of Foucault and Bourdieu. That choice is not a fortuitous one, since the mentioned theories are in line with a previous understanding about discourses, namely, that discourses are not only speeches, but ideological products of battles for power. Once the thesis theoretical basis is exposed, it follows a narrative of the selected criminal suit and media manifestations about it. After that, the discourse analysis begins. It has as its focus two institutions, the media and the courts, which are chosen because they both have a special relationship with sexual violence, of broadcasting (the media) and judgment (the courts). Also taken into account are social discourses, particularly, but not exclusively, discourses about crime and sexuality, since the recognition of sexual violence comes from the combination of those two concepts. The work ends by claiming that what is perceived as crime and sexuality results from a relationship of power, the same being valid for sexual violence.